Gene Variant of the Bradykinin B2 Receptor Influences Pulmonary Arterial Pressures in Heart Failure Patients - Thomas P. Olson (Clinical Medicine Insights: Circulatory, Respiratory and Pulmonary Medicine, 2009)
Background Pulmonary arterial pressure (PAP) varies considerably in heart failure (HF) despite similar degrees of left ventricular (LV) dysfunction. Bradykinin alters vascular tone and common variations in the kinin B2 receptor (BDKRB2) gene exists. We hypothesized that genetic variation in this receptor would influence PAP in HF. Methods 131 HF patients (>1yr history systolic HF), without COPD, not currently smoking, BMI < 40, without atrial fibrillation completed the study which included a blood draw for genotyping and neurohormones (ACE, A-II, Bradykinin, ANP, BNP, and catecholamines), an echocardiogram for cardiac function and systolic PAP (PAPsys). Results Mean LVEF was 29% ∓ 12%, NYHA class 2 ∓ 1, age 56 ∓ 12 yr, BMI 28 ∓ 5 kg/m 2 . Forty-six patients (35%) were homozygous for the +9 allele, 58 (44%) were heterozygous (+9/-9) and 27 (21%) were homozygous for the -9 allele of the BDKRB2. PAPsys averaged 42 ∓ 13, 38 ∓ 12, and 35 ∓ 11 mmHg for +9/+9, +9/-9 and -9/-9, respectively (p = 0.03). There was a trend towards gene effect for plasma ACE with the highest values in +9/+9 and lowest in -9/-9 patients (9.5 ∓ 10.7, 7.1 ∓ 8.7, and 5.4 ∓ 6.4 U/L, respectively, p = 0.06). There were no differences in plasma bradykinin or A-II, LVEF, or NYHA across genotypes. Conclusion These data suggest the +9/+9 polymorphism of the BDKRB2 receptor influences pulmonary vascular tone in stable HF.